Wooden Church Architecture of the Russian North in the Petrine Epoch - Khodakovsky, Evgeny V. (Actual Problems of Theory and History of Art, 2023)
The article presents an overview of wooden church construction in the Russian North during the reign of Peter I. The research includes both the monuments built with the personal participation or under the supervision of the tsar, and the most artistically and historically significant northern churches of the first quarter of the 18th century. The analysis of the wooden architecture of the Russian North of the Petrine era and subsequent decades showed that the Petrine transformations were practically not reflected in the structure and composition of most of the churches that were built in the northern provinces during the 18th century. The direct participation of Peter the Great in the construction had an impact on the “foreign” character of only two churches: in the Novodvinsk fortress and in Martzialnye Vody. The appearance of other buildings that are usually associated with Peter the Great — the Peter and Paul Cathedral in Petrozavodsk, the churches of the Vytegorsky and Kizhi churchyards, and the Church of St. Andrew (Solovki) — is due to the very nature of the historical development of Russian architecture in the second half of the 17th – early 18th centuries. The stability of church-building traditions in the monuments of the 18th century testifies to the persistence of Old Russian inertia, which proved to be beyond the control of the powerful energy of the Petrine era. But even the changes that nevertheless took place in the wooden architecture of the middle – second half of the 18th century, were not associated with Peter’s transformations, but with general processes that determined the nature of the Russian architecture at that time and were rooted in the gradual spread of Baroque through the architecture of stone churches in provincial towns. These influences were also of a local nature, while the general trend in the development of northern church building still showed conservatism and consistency. The decisive influence on the fate of wooden church architecture in Russia was exerted not by Peter the Great, but by Paul I, who issued a decree on December 25, 1800, prohibiting the construction of wooden parish churches. Thus, it was his ban that changed the centuries-old course of development of carpentry traditions for two generations, after which, from the 1830s, under the regulations of the Nikolay I, the resumption of wooden church building followed a completely different path. The research was supported by the Russian Science Foundation, project Nr. 21-48-04402 “Saints and heroes from Christianization to Nationalism: Symbol, Image, Memory (Nord-West Russia, Baltic and Nordic countries)”.